Removal of steroid estrogens from municipal wastewater in a pilot scale expanded granular sludge blanket reactor and anaerobic membrane bioreactor - Ito, Ayumi; Mensah, Lawson; Cartmell, Elise; Lester, John N. (Taylor and Francis, 2015)
Anaerobic treatment of municipal wastewater offers the prospect of a new paradigm by reducing aeration costs and minimizing sludge production. It has been successfully applied in warm climates, but does not always achieve the desired outcomes in temperate climates at the biochemical oxygen demand (BOD) values of municipal crude wastewater. Recently the concept of fortification' has been proposed to increase organic strength and has been demonstrated at the laboratory and pilot scale treating municipal wastewater at temperatures of 10-17°C. The process treats a proportion of the flow anaerobically by combining it with primary sludge from the residual flow and then polishing it to a high effluent standard aerobically. Energy consumption is reduced as is sludge production. However, no new treatment process is viable if it only addresses the problems of traditional pollutants (suspended solids - SS, BOD, nitrogen - N and phosphorus - P); it must also treat hazardous substances. This study compared three potential municipal anaerobic treatment regimes, crude wastewater in an expanded granular sludge blanket (EGSB) reactor, fortified crude wastewater in an EGSB and crude wastewater in an anaerobic membrane bioreactor. The benefits of fortification were demonstrated for the removal of SS, BOD, N and P. These three systems were further challenged with the removal of steroid estrogens at environmental concentrations from natural indigenous sources. All three systems removed these compounds to a significant degree, confirming that estrogen removal is not restricted to highly aerobic autotrophs, or aerobic heterotrophs, but is also a faculty of anaerobic bacteria.
Keywords: anaerobic treatment; fortification; municipal wastewater; steroid estrogens; temperate